Analysis of Customer Preferences in Choosing a Digital Bank based on the Level of Digital Financial Literacy in Bone Regency - Arafah (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
This study aims to analyze the effect of digital financial literacy level on customer preferences in choosing digital banks in Bone Regency. The background of this research is based on the rapid development of financial technology and the increase in digital banking services, which requires a better understanding of digital financial literacy from the public. This research uses a quantitative approach with a survey method through distributing questionnaires to 100 respondents who are customers in the Bone Regency area. The data analysis technique used is simple linear regression analysis. The results showed that digital financial literacy has a significant effect on customer preferences in choosing digital banks. This indicates that the higher a person's level of digital financial literacy, the more likely they are to choose digital bank services in their financial activities. This study recommends increasing digital financial education and counseling to the public to encourage the use of technology-based financial services more optimally and safely.